Closeness of Some Graph Operations - Chavdar Dangalchev (Computing Open)
Closeness is an important measure of network centrality. In this paper, we will calculate the closeness of graphs, created by using operations on graphs. We will prove a formula for the closeness of shadow graphs. We will calculate the closeness of line graphs of some well-known graphs (like path, star, cycle, and complete graphs) and the closeness of line graphs of two of these graphs, connected by a bridge (like lollipop, tadpole, broom, and bistar graphs).